Groundwater quality assessment from Tarali river sub basin of Krishna river basin, western Maharashtra (India) - Golekar, Rushikesh; Bartakke, Vikrant Vijaykumar; Patil, Sanjaykumar Narayan; Baride, Mukund Vasant (International Journal of Advanced Geosciences, 2014)
The aims of present study to assessing drinking and irrigation water quality in Tarali river sub basin of Krishna river Basin, Western Ma-harashtra (India). The study area is lying between Latitude 17°23' to 17°38' N and Longitude 73°48' to 74°27' E. The area having steep to moderate slope and elevation ranges from 584-1171m above the Mean Sea Level (MSL). Basin exhibits hilly and mountain terrain forming ridges and Western Ghats with deep valley, plateaus and plain. The whole area can obtained in topographical sheets i.e. 47 G/14, 47 G/15 47 K/2, 47 K/3 covering area about 627 sq.km, acquired from survey of India. The climate of basin is semi-arid to sub-humid climate. Average annual rainfall is 800-1800mm in the study area. Field work was carried out during post monsoon 2012 (winter) and collect the groundwater samples from the both bank of Tarali River Sub Basin. Hydrogeochemical analysis was carried out using standard analytical techniques. A total 20 groundwater samples were collected from public water supply wells in the area under study. Draw the various plots on the basis of obtained results by using Aquachem geoscientific software. Keywords: Groundwater geochemistry, piper trilinear diagram, Wilcox diagram, box whisker plot, Tarali river sub basin, western Maharashtra (India).